Time distortion in student YouTube use: The effects of use motivation, personality, and pattern of use on study efficiency - McGill, Tanya; Klobas, Jane; Moghavvemi, Sedigheh (Australasian Journal of Educational Technology, 2023)
This paper examines study efficiency and time distortion experienced by student users of YouTube. Using multi-group structural equation modelling on data from 792 Malaysian university students, the study identified links between YouTube use motivation, conscientiousness (a personality trait), time distortion, and perceived study efficiency. It also shows how these characteristics and the links between them varied when students were grouped by pattern of use, defined (using two-step cluster analysis) as occasional, regular, or problematic. Time distortion had a negative effect on perceived study efficiency, but conscientiousness counteracted this effect - particularly for occasional users, the only group with positive perceived study efficiency in this study. Motivation to use YouTube for learning was not associated with time distortion, whilst using YouTube for escape and entertainment increased motivation. Occasional users were less motivated than others to use YouTube for these purposes and therefore less likely to experience the entertainment use flow on effects of time distortion to perceived study efficiency. Implications for practice or policy: Motivating students to use YouTube for learning is unlikely to reduce study efficiency. Use of diagnostic tools to understand a student's pattern of social media use, as well as motivation for use, personality and sense of time distortion, could help advisers identify reasons for low study efficiency. Digital literacy education focused on increasing self-discipline and goal-orientation could help students reduce poorly controlled use of social media for entertainment and escape, and hence improve study efficiency.